A dual responsive fluorescent probe for selective detection of cysteine and bisulfite and its application in bioimaging. Issue 2 (4th January 2022) - Wang, Xiaofeng; Li, Mingshun; Duan, Tingting; Zou, Yuxia; Zhou, Xuejun
Abstract : A coumarin-based dual responsive fluorescent probe with a simple structure was developed for the detection of Cys and HSO3 − . Abstract : A coumarin-based dual responsive fluorescent probe with a simple structure was developed for the detection of Cys and HSO3 − . Under simulated physiological conditions, Cou-F displayed an on–off fluorescence response to Cys at 521 nm and an off–on fluorescence response to HSO3 − at 500 nm. Furthermore, Cou-F had the advantages of high sensitivity, strong specificity and rapid response. The detection limits of Cou-F toward Cys and HSO3 − were 0.54 μM and 0.65 μM, respectively. Cou-F enabled high selective responses to Cys and HSO3 − over other biologically related species. The response times of Cou-F toward Cys and HSO3 − were 80 s and 100 s. The fluorescence imaging of Cys and HSO3 − was achieved in living RAW246.7 cells.